The Relationship of Leadership Styles and Organizational Culture Case Study of an Oil and Gas Company in Indonesia - Darwis, Tommy K; Djajadiningrat, Surna Tjahja (SBM ITB, 2010)
This study explores relationship between leadership styles and organizational culture in an oil and Gas Company in Indonesia. The respondents are employees of an oil and Gas Company in Indonesia. This study use Multifactor leadership questionnaires to define leadership styles and Denison's Organizational Culture Model to measure Organizational Culture. These questionnaires were used to measure leadership styles of immediate or direct supervisor and organizational culture of unit or division. The data were analyzed with descriptive and use correlational analysis.Arelationship exists between the leadership styles of immediate or direct supervisor and organizational culture. In three Leadership styles of Multifactor leadership, Positive correlation was found between Transformational Leadership Style and Organizational Culture. Transformational Leadership found as strong predictor of organizational culture. A positive correlation also found between Transactional Leadership Style and Organizational Culture and conversely, Laissez-Faire Leadership style has negative correlation with organizational culture. Transformational, Transactional Leadership and high level of organizational culture will be make good impact for maintaining and achieving excellent organizational performance for company.Keywords: Leadership Styles, Organizational Culture, Transformational Leadership, Oil and gas Company in Indonesia